Rethinking employability: how students build on interest in a subject to plan a career - Quinlan, Kathleen M.; Renninger, K. Ann (Higher education, 2022)
As universities prioritise employability, there is increased attention to promoting students’ career decidedness. In this mixed method, cross-sectional study, we explore whether and how students’ interest in their academic subject affects their career decidedness. Using surveys of 428 undergraduates studying sciences in a UK university (60% F, average age = 19.9) and case examples from follow-up interviews with 15 students, we examine students’ interest development and its relation to their career decidedness and their desire for meaningful, interesting work. Findings showed that most students who were studying science in university had a well-developed interest that had motivated their choice of programme, and their subject interest and career decidedness were linked. Regression analyses indicated that students’ interest in their subject was a significant predictor of career decidedness, mediated by students’ desire to pursue that interest in their career. Open-ended comments on the surveys suggested that decidedness was informed by coursework, proactive career exploration, work experience, interest, feasibility, and familial contacts. Interviews confirmed these factors and illustrated how they contributed to students’ career decidedness. We propose implications for academics and career counsellors who might help students refine their interest by considering connections between their academic subject, interest, and related career options. We argue that educators and policy-makers need to reframe employability interventions and think beyond teaching students skills or attributes that lead to employment. Educators can start with students’ interest in their subject and support students’ exploration of how they can continue to pursue that interest in various careers.